Stress-induced neuroinflammatory priming is time of day dependent. (April 2016) - Fonken, Laura K.; Weber, Michael D.; Daut, Rachel A.; Kitt, Meagan M.; Frank, Matthew G.; Watkins, Linda R.; Maier, Steven F.
Highlights: Timing of stressor exposure influences neuroinflammatory priming. Microglia inflammatory responses are similarly regulated by time of stress exposure. The corticosterone response is enhanced following stress during the light phase. Glucocorticoids directly down-regulate genes involved in microglia inhibition. Abstract: Circadian rhythms are endogenous cycles of physiology and behavior that align with the daily rotation of the planet and resulting light–dark cycle. The circadian system ensures homeostatic balance and regulates many aspects of physiology, including the stress response and susceptibility to and/or severity of stress-related sequelae. Both acute and chronic stressors amplify neuroinflammatory responses to a subsequent immune challenge, however it is not known whether circadian timing of the stressor regulates the priming response. Here, we test whether stress-induced neuroinflammatory priming is regulated by the circadian system. As has been previously shown, exposure to 100 inescapable tails shocks (IS) increased hippocampal cytokines following a subsequent inflammatory challenge. However, this effect was limited to animals that experienced the stressor during the light phase. Rats exposed to stress during the dark phase did not alter inflammatory potential following lipopolysaccharide (LPS) challenge. To determine whether microglia might be involved in diurnal differences in neuroinflammatory priming, microglia were isolated 24 h after stress that occurred either during the middle of the light or dark phase. Only microglia isolated from animals stressed during the light phase demonstrated an exaggerated inflammatory response when treated ex vivo with LPS. To determine possible circadian dependency of microglia responsiveness to glucocorticoids – the likely proximal mediator for stress associated neuroinflammatory priming – microglia were isolated during the middle of the light or dark phase and treated ex vivo with corticosterone. Glucocorticoids treatment downregulated CX3CR1 and CD200R, two genes involved in microglial inflammatory "off" signaling; however, there was no effect of time of day on expression of either gene. Importantly, while absolute concentrations of corticosterone were comparable following IS during the light and dark phase, the magnitude of change in corticosterone was greater during the light phase. This work highlights the importance of studying circadian rhythms to elucidate biological mechanisms of stress.